Empowering Educators: The Mediating Role of Self-Efficacy in Reflective Practice and Teacher Identity Development - Daming, Hamdi M.; Hermansyah, Sam; Solihatun, Solihatun (Eduscape : Journal of Education Insight, 2025)
This study investigates the mediating roles of reflective practice and teacher self-efficacy in the development of Teacher Professional Identity (TPI). Although participation in Continuing Professional Development (CPD) is widespread, little is known about how these experiences contribute to meaningful identity transformation for teachers. Addressing this gap, the study proposes a mediation model in which reflective practice indirectly enhances TPI through the intermediary construct of self-efficacy. Utilizing a cross-sectional design with a sample of 420 in-service teachers, the research employed validated instruments to measure reflective practice, self-efficacy, and TPI. Structural Equation Modeling (SEM) and PROCESS macro (Model 6) were used to analyze the direct and indirect effects. Bootstrapped confidence intervals and model fit indices (CFI = 0.96, TLI = 0.94, RMSEA = 0.045) confirmed the robustness of the proposed model. Results revealed a significant direct effect of reflective practice on TPI (β = 0.21, p = 0.042), and a stronger indirect effect mediated by self-efficacy (β = 0.34, p < 0.001). The findings support the hypothesis that self-efficacy plays a central role in converting reflective experiences into professional identity development. This mediation framework contributes to the theoretical discourse on TPI and underscores the importance of incorporating reflective and efficacy-building components into CPD. The study offers key implications for CPD design, advocating for culturally responsive and psychologically enriching programs that prioritize structured reflection and empower teachers to engage deeply with their evolving roles. Such initiatives are likely to yield sustained improvements in instructional quality and teacher resilience.